Stability of foliar nitrogen:sulfur ratio in spring red wheat and sulfur dilution curve - Reussi Calvo, Nahuel Ignacio (2012)
A key aspect of any sulfur (S) availability indicator is its stability throughout the crop cycle. Nine experiments were conducted with the objective to evaluate the stability of the nitrogen (N):S ratio in aerial biomass (W) in spring wheat, and to define the critical curve of S dilution. As the crop cycle progressed, a decrease (P < 0.05) in total N:S was determined. This lack of stability was explained by a lower S dilution in relation to N (P < 0.05). A decrease (P < 0.05) in N accumulation rate in relation to S was obtained as the crop cycle progressed, which points out that S accumulation in relation to N is later. A first approach was determined to the definition of the S dilution critical curve (Sc) from tillering beginning to stem elongation end (Sc = 0.37 W−0.169; r2 = 0.71 and n = 24).